How Much Can Marketability Affect Security Values? - Longstaff, Francis A. (Journal of Finance, 1995)
How marketability affects security prices is one of the most important issues in finance. We derive a simple analytical upper bound on the value of marketability using option-pricing theory. We show that discounts for lack of marketability can potentially be large even when the illiquidity period is very short. This analysis also provides a benchmark for assessing the potential costs of exchange rules and regulatory requirements restricting the ability of investors to trade when desired. Furthermore, these results provide new insights into the relation between discounts for lack of marketability and the length of the marketability restriction.